2010
DOI: 10.1007/s12350-010-9239-x
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide imaging of cardiac autonomic innervation

Abstract: Cardiac autonomic function plays a crucial role in health and disease, with abnormalities both reflecting the severity of the disease and contributing specifically to clinical deterioration and poor prognosis. Radiotracer analogs of the sympathetic mediator norepinephrine have been investigated extensively, and are at the brink of potential widespread clinical use. The most widely studied SPECT tracer, I-123 metaiodobenzylguanidine ((123)I-mIBG) has consistently shown a strong, independent ability to risk stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…10,25 Functional cardiac imaging studies with different tracers suggested that increased global cardiac uptake has a high negative predictive value in terms of cardiac events. 26 MSNA burst rates exceeding 49 bursts per minute were associated with reduced 1-year survival rates in 122 heart failure patients. 11 Our observation that resting MSNA was not profoundly increased compared with matched healthy controls is reassuring and indicates that continuousflow LVAD therapy might decrease sympathetic drive in heart failure patients.…”
Section: Discussionmentioning
confidence: 96%
“…10,25 Functional cardiac imaging studies with different tracers suggested that increased global cardiac uptake has a high negative predictive value in terms of cardiac events. 26 MSNA burst rates exceeding 49 bursts per minute were associated with reduced 1-year survival rates in 122 heart failure patients. 11 Our observation that resting MSNA was not profoundly increased compared with matched healthy controls is reassuring and indicates that continuousflow LVAD therapy might decrease sympathetic drive in heart failure patients.…”
Section: Discussionmentioning
confidence: 96%
“…Recent reviews have summarized the mechanism by which I-123 MIBG is taken up by the nerve terminal, the utility of this agent, and the technical aspects of its imaging. [24][25][26][27] One of the strengths of the current study by dos Santos 28 is that all of the subjects were relatively young (mean age of 16), when identification of early anthracycline-induced cardiomyopathy would be most critical. The subjects were a median of 5.3 years out from their chemotherapy.…”
Section: See Related Article Pp 256-264mentioning
confidence: 99%
“…Most autonomic radiotracers under investigation image pre-synaptic anatomy and function, illustrated in Figure 1 19,20 (although there is ongoing work on PET tracers that bind to post-synaptic a and b receptors). NE is produced in the pre-synaptic terminal, and is concentrated and stored in vesicles, often with ATP.…”
Section: Development Of Autonomic Radiotracersmentioning
confidence: 99%